Minutes of General Council (extract)
015b_0004_001 27th January 1937 G.C. Minutes 78. JOINT MEETING OF THE LABOUR & SOCIALIST INTERNATIONAL AND INTERNATIONAL FEDERATION OF TRADE UNIONS. Report of Joint meeting of the Labour and Socialist International and the International Federation of Trade Unions, held at the C.G.T. Offices, Paris, on the 14th January, 1937, was presented, and in view of its confidential nature, the members were asked to hand back their copies at the end of the meeting. 292/946/15b/4